MULTI- CRITERIA DECISION BASED APPROACH TO SELECTING THE TYPE OF INDUSTRIAL HALLS USED IN FOOD INDUSTRY - Milinković, Ozrislava; Jakić, Branislav; Vuksanović, Slobodan; Macura, Dragana; Šelmić, Milica (Economics of Agriculture, 2017)
Design of production facility in food industry covers all stages of its development, from concept and selection of technological processes to the construction and putting facility in to operation. The objectives pursued in the selection and construction of multipurpose industrial facility is reducing costs as well as the negative impact that the building has on the environment. In other words objectives are connecting engineering theory and practice, in order to achieve savings in the use of resources necessary for the construction, reducing costs of maintenance and usage of the facility from the perspective of the whole life cycle. Introducing the concept of sustainability in food industry must start from choosing sustainable plant where food is processed, packed and stored. This is important because in a polluted environment is not possible to produce high-quality food. Applying multi-criteria decision methods is enabling us to objectively evaluate the impact that industrial buildings used in the food industry have on the environment, as well as their ability to meet production and environmental criteria. The paper is devoted to an analysis of commonly used industrial halls in food industry and building systems in terms of environmental protection and sustainable development.